2017
DOI: 10.1088/1555-6611/aa6583
|View full text |Cite
|
Sign up to set email alerts
|

TunableQ-switched erbium-doped fiber laser based on curved multimode fiber and graphene oxide saturable absorber

Abstract: A tunable Q-switched erbium-doped fiber laser using a singlemode-multimode-singlemode fiber structure as a wavelength tuning filter and a graphene oxide saturable absorber is proposed and demonstrated. The system allows the Q-switched laser to be tuned between the wavelengths of 1550.78 nm and 1560.62 nm, giving a tuning range of 9.84 nm. At a Q-switched laser wavelength of 1552.75 nm, a repetition rate of 39.1 kHz and pulse width of 3.6 µs, as well as an average output power of 1.32 mW and pulse energy of 33.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…While the physical and chemical characteristics of 2D materials have long been studied and are well understood, the optical properties of these materials was first properly documented in graphene [7][8][9][10][11]. Since then, various other 2D materials have also been studied for their inherent optical properties, with transition metal dichalcogenides (TMDs) in particular observed to be highly suited towards photonics applications.…”
Section: Introductionmentioning
confidence: 99%
“…While the physical and chemical characteristics of 2D materials have long been studied and are well understood, the optical properties of these materials was first properly documented in graphene [7][8][9][10][11]. Since then, various other 2D materials have also been studied for their inherent optical properties, with transition metal dichalcogenides (TMDs) in particular observed to be highly suited towards photonics applications.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] A year later, in 2017, Ahmad et al, demonstrated a similar bending‐based tuning of an Er MMI fiber laser, where they achieved laser tuning over 9.8 nm, in the range from 1552 to 1562 nm, in Q‐switching (QS) operation with a single laser output. [ 28 ]…”
Section: Wavelength‐tuned MMI Fiber Lasersmentioning
confidence: 99%
“…Summary of the central wavelength and the tuning range of wavelength‐tuned MMI fiber lasers tracked over time. Squares (orange) markers indicate ytterbium MMI fiber lasers: a) Selvas et al [ 13 ] b) Anzueto et al [ 14 ] c) Mukhopadhyay et al [ 29 ] d) Chakravarty et al [ 30 ] Circles (green) markers indicate Erbium MMI fiber lasers: e) Castillo et al [ 15 ] f) Castillo et al [ 16 ] g) Walbaum et al [ 26 ] h,i) Ma et al, [ 21,22 ] j) Antonio et al, [ 20 ] k) Ahmad et al [ 28 ] l) Khattak et al [ 31 ] m) Li et al [ 34 ] n) Zhang et al [ 32 ] Triangles (purple) markers indicate Thulium MMI fiber lasers: o) Ma et al [ 23 ] p) Zhang et al [ 33 ] q) Li et al [ 27 ] r) Ibarra et al [ 24 ] s,t) Sakata et al [ 25 ] u) Li et al [ 35 ] v,w) Sakata et al [ 36 ] The diamond and down triangle indicate exceptional cases where special light sources were used for Erbium, x) Antonio et al, [ 20 ] and Thulium, y) Yan et al [ 37 ] , respectively (see text for details).…”
Section: Wavelength‐tuned MMI Fiber Lasersmentioning
confidence: 99%
“…The wavelength tunable is constructed by the combination of a tunable filter with either an active, passive Q-switched, or mode-locked system. The tunable filter which frequently used to tune the wavelength of the pulse laser is curved multimode fiber [10], fiber Bragg grating (FBG) [11], multimode interference (MMI) filter [12], rotating mirrors in combination with a diffraction grating [13,14], sagnac interferometer [15,16], tilted fiber Bragg grating (TFBG) [17], and tunable bandpass filter (TBF) [18][19][20][21][22][23][24]. Passive Q-switched configuration is based on the incorporation of a saturable absorber (SA) [25].…”
Section: Introductionmentioning
confidence: 99%